Relaç\~ao dinâmica: Fertilizantes minerais e agricultura brasileira - Cristiane Mitie Ogino; José Garcia Gasques; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
– In 2022, international mineral fertilizer prices reached high levels, which caused concern in the agricultural market. In this context, the present study analyzed the behavior of the mineral fertilizer market in Brazilian agricultural production. Using the SVAR model, the relationship between the mineral fertilizer prices, the quantity demanded of mineral fertilizers, the attractiveness of exporting commodities, the planted area and the quantity produced in agriculture was examined. The analysis of the impulse-response function indicated that a shock in the import price of fertilizers negatively impacts the demand quantity of the input. Furthermore, it was found that a shock in the quantity demanded for fertilizers positively impacts the agricultural quantity produced. The results highlighted the importance of strategic plans in the fertilizer sector to support food security in Brazil.
Keywords: Q11; Q13; Q18; 330; inputs; prices; agricultural productivity; SVAR